Evaluation of puva therapy in palmoplantar dermatoses - Dogra Alka; Dua Aman; Chopra S (Wolters Kluwer Medknow Publications, 2006)
BACKGROUND: Palmoplantar dermatoses often show therapeutic problem. PUVA therapy represents an effective remedy for refractory dermatoses. PURPOSE: To evaluate the response of palmoplantar dermatoses to PUVA therapy. METHODS: A propsective study undertaken on 50 patients from the Outpatients Department of Dermatology in Dayanand Medical College and Hospital, Ludhiana to study the effect of PUVA therapy in plamoplantar dermatoses. Out of the total of 50 patients, 26 patients (52%) had chronic plaque psoriasis, 19 patients (38%) had vitiligo (acrofacial variety) and 5 patients (10%) had lichen planus. Each patient was given PUVA therapy 3 times of week on alternate days for 6-12 months or remission whichever was earlier and then followed up for 6 months. RESULTS: About 62.5% patients of psoriasis, 55.5% of vitiligo and 60% of lichen planus showed improvement. Main side effects were nausea and erythema (20%). PUVA Therapy had to be stopped in one patient due to flaring of psoriasis. After six months of follow-up, 60% of patients were maintained in remission in psoriasis; none of the patients of vitiligo showed any loss of pigmentation; and, all the patients who showed improvement in lichen planus were maintained in remission. CONCLUSION: PUVA Therapy is a successful treatment for plamoplantar dermatoses like psoriasis, vitiligo and lichen planus. LIMITATION: Open study having no control and small sample size.